In vitro studies and short term studies - Caroli, Sergio (Henry Stewart Talks, 2013)
In vitro studies, Short-term studies, Acute toxicity studies, Acute ecotoxicological studies, Genetic toxicity testing, Standardized general study plan, Study-specific supplement, Standardised final report, Process-based inspections, Standard operating procedures, Test item, Reference item, Contamination of batches, Characterisation of culture media, Predictive capacity of in-vitro studies, Assessment of health effects